Concilier flexibilité du travail et cohésion sociale. Les expériences et les enjeux spécifiques en Europe centrale et orientale = Reconciling labour flexibility with social cohesion. The experiences and specificities of central and eastern Europe - Council of Europe (Strasbourg, 2007)
"Even though the work place has become significantly more flexible in the former socialist countries of central and eastern Europe, the ideas on “flexicurity” and strategies of reconciliation are usually only developed in the context of the western European welfare states. However, when considering the differences of the transformation process, it is clearly indispensable to go beyond a one-size-fits-all strategy. The realities of central and eastern Europe and their social institutional systems must I taken into account. This volume contributes to filling this gap and to starting a pan-European reflection on the concepts and issues of labour flexibility and social cohesion. It contributes to the understanding the specificities of certain realities in central and eastern Europe, including Turkey, in order to conceive adequate strategies for conciliation."